Figure skating injuries - Bloch, R. M. (Physical Medicine & Rehabilitation Clinics of North America, 1999)
Figure skaters who train regularly sustain primarily lower extremity injuries, especially overuse injuries. Quadriceps and hamstring stretching may help prevent or decrease anterior knee pain. Foot and ankle problems may be related to the rigidity of the leather skating boot. The need for trunk strength to maintain body position is frequently under-emphasized. Air quality may also be a problem for those who skate in enclosed rinks.